The Magnetism of Ponggok Tourism Village: From e-WOM to Destination Image Shaping Revisit Intention - Novita Sari, Puspa; Karsono, Lorena Dara Putri (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study aims to analyze the factors influencing revisit intention, such as e-WOM and destination familiarity, with destination image as an intervening variable. The research was conducted in Ponggok Klaten tourism village. A quantitative approach was employed, utilizing the SEM-PLS model. The study's results were tested using the Smart PLS 3 application. Data collection was carried out through questionnaires, field observations, and interviews. The population of this study includes visitors to the Ponggok Klaten Tourism Village. The sampling technique used was purposive sampling, with the criteria being visitors who had visited the Ponggok Klaten Tourism Village at least once and were interested in revisiting. The sample obtained in this study comprised 248 respondents. The results indicate that e-WOM and destination familiarity positively and significantly impact destination image. Similarly, destination image significantly affects revisit intention. This suggests that destination image mediates the influence of e-WOM and destination familiarity on revisit intention. Thus, efforts to increase revisit intention can be achieved by enhancing e-WOM and destination familiarity through destination image. This research is limited to a specific tourism destination. This study contributes to tourism village managers by demonstrating how online reviews and information can affect tourists' perceptions and their intention to revisit. This study positions destination image as an intervening or mediating variable that explains the relationship between e-WOM and familiarity with revisit intention. It provides new perspectives on the crucial role of destination image in linking digital information and direct experiences with tourists' decisions. Using this mediating variable helps reveal the more complex mechanisms through which the two independent variables influence revisit intention.